Trenirovka skorostnych vozmožnostej begunov na 400 m na osnove Smart-technologij ekspress-informacii - Kryazhev, V. D.; Rostovtsev, V. L.; Kryazhev, S. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In the training of 4 qualified runners-students specializing in the 400 m distance for 5 weeks used 10 training sessions, which contained running on short stretches (10 times 20 m from the turn) to increase the maximum speed. The training method used the method of urgent information about the speed of running, frequency and length of running steps, implemente on the basis of an electronic stopwatch with photo sensors and video recording on a smartphone with a frequency of 240 k/s. The sportsmen`s increased running speed on each 20-metre distance due to varying effort, length and frequency of running steps. During the experiment, the maximum speed of running increased in the group from 9.32 ± 0.23 m/s to 9.87 ± 0.29 m/s. Improvement in speed is provided by increasing the frequency (from 4.21 ± 0.019 to 4.38 ± 0.101 1/s) and length of running steps (from 2.21 ± 0.063 to 2.23 ± 0.057 m) with a greater frequency effect. The high reliability of the speed boost is confirmed by the improvement in the average time of the 7 best attempts from the initial to the key session (from 2.191 ± 0.028 to 2.092 ± 0.0 s at P ? 0.01). The result in the 200 m run for the participants of the experiment improved from 23.22 ± 0.27 s to 22.95 ± 0.24 s or 0.27 s. The possibility of developing a mobile application for a smartphone to automatically record running speed and running parameters during the friction process is discussed.